PERAN ORANGTUA DALAM MENSTIMULASI PERKEMBANGAN MOTORIK ANAK USIA DINI - Saripah Saripah (Samawa (Sakinah, Mawaddah Warahmah), 2021)
Every parents or educator wants their child or learners to grow up to be a smart, healthy, independent, creative child. To make this happen, parents or educators need to know and understand well about the world of their children. Because the world of children is different from adults. Children's world is play. And basically the parenting or educators is to direct these children as superior generations. The stimulation of the development of motor skills in early childhood is often forgotten and even ignored by parents or educators. This is because they do not understand that stimulation of motor skills development is inseparable in early childhood education.